Mammalian lineages and the biostratigraphy and biochronology of Cenozoic faunas from the Riversleigh World Heritage Area, Australia. (19th May 2015) - Arena, Derrick A.; Travouillon, Kenny J.; Beck, Robin M. D.; Black, Karen H.; Gillespie, Anna K.; Myers, Troy J.; Archer, Michael; Hand, Suzanne J.
Abstract : Lineage zones within nine contemporaneous mammalian lineages represented in the Cenozoic fossil vertebrate record from the Riversleigh World Heritage Area in northern Australia are used to resolve a series of faunal intervals from the Late Oligocene to Late Miocene. The results agree with previous interpretations of Cenozoic biostratigraphy, provide evidence for the presence of time horizons subdividing some of the four previously recognized Riversleigh biochrons A–D and also provide evidence supporting the allocation of a greater number of Riversleigh faunas to intervals within the Riversleigh biochronology than other methods in previous work. This approach demonstrates the biostratigraphical potential of evolutionary lineages.